Stark Absorption Study of Perylene Doped in a Poly (Methyl Methacrylate) Polymer Film at Different Concentrations (Journal of Bangladesh Academy of Sciences, 2020)
In this article, electric field modulated absorption (Stark absorption, SA) study of perylene doped in a poly (methyl methacrylate) (PMMA) polymer film at the concentrations of 1.0 mol%, 2.0 mol% and 3.0 mol% is presented. The field effects on the absorption spectra were found to originate mostly from the Stark shift induced by a change in molecular polarizability between the ground and excited states. The analyses of SA spectra with the aid of Liptay formalism yielded essentially the same magnitude of the average change in molecular polarizability (Δα), evaluated for the S0 -> S1 transition, for all the concentrations. This finding implies that Δα of perylene molecule doped in a PMMA film does not depend on concentration. Moreover, the yielded positive Δα for both the preparations implies that SA spectroscopy is an essential technique to probe spectroscopically that perylene possesses larger molecular polarizability in the excited states than in the ground state.Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 133-139, 2019